2004
DOI: 10.1111/j.1467-7687.2004.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

The Thatcher illusion and face processing in infancy

Abstract: Adults readily detect changes in face patterns brought about by the inversion of eyes and mouth when the faces are viewed upright but not when they are viewed upside down. Research suggests that this illusion (the Thatcher illusion) is caused by the interfering effects of face inversion on the processing of second-order relational information (fine spatial information such as the distance between the eyes). In the current study, 6-month-olds discriminated 'thatcherized' faces when they were viewed upright but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 48 publications
2
47
1
Order By: Relevance
“…(a) The Thatcher illusion in humans As mentioned earlier, the Thatcher illusion has been shown psychophysically using rating tasks (Parks et al 1985;Bartlett & Searcy 1993;Murray et al 2000), recognition rates (Rhodes et al 1993), habituation (Bertin & Bhatt 2004) and perceptual comparison tasks (Bartlett & Searcy 1993;Searcy & Bartlett 1996;Leder et al 2001;Edmonds & Lewis 2007) and has become an important tool for the exploration of processing strategies. A continuous rotation along the image-plane axis induces a shift from holistic and part-based processing to part-based processing strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) The Thatcher illusion in humans As mentioned earlier, the Thatcher illusion has been shown psychophysically using rating tasks (Parks et al 1985;Bartlett & Searcy 1993;Murray et al 2000), recognition rates (Rhodes et al 1993), habituation (Bertin & Bhatt 2004) and perceptual comparison tasks (Bartlett & Searcy 1993;Searcy & Bartlett 1996;Leder et al 2001;Edmonds & Lewis 2007) and has become an important tool for the exploration of processing strategies. A continuous rotation along the image-plane axis induces a shift from holistic and part-based processing to part-based processing strategies.…”
Section: Discussionmentioning
confidence: 99%
“…By means of inversion, also referred to as face inversion, holistic processing is impaired, thus leaving local feature inversions undetected. In humans, the Thatcher illusion has been investigated extensively with psychophysical measurements of ratings (Parks et al 1985;Bartlett & Searcy 1993;Murray et al 2000), recognition (Rhodes et al 1993), habituation (Bertin & Bhatt 2004) and perceptual comparison tasks (Bartlett & Searcy 1993;Searcy & Bartlett 1996;Leder et al 2001;Edmonds & Lewis 2007), as well as neurophysiological measurements (Milivojevic et al 2003;Carbon et al 2005;Boutsen et al 2006;Gu et al 2007) and functional magnetic resonance imaging (Rotshtein et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Inversion is shown to affect infants' sensitivity to second-order configural changes of faces in 5-month-olds, but not 3-month-olds (Bhatt et al, 2005;Hayden et al, 2007). Results are mixed when sensitivity to upright and inverted Thatcherized faces have been tested in infants between 0 and 6 months (Bertin & Bhatt, 2004;Leo & Simion, 2009). On the other hand, at 7-8 months, but not at younger ages, there is clear evidence that inversion affects holistic face processing (Cashon & Cohen, 2004;Cohen & Cashon, 2001;Ferguson et al, 2009).…”
Section: Summary Of Findingsmentioning
confidence: 91%
“…Bertin and Bhatt found that 6-month-olds discriminated between the two test faces in the upright condition, but not in the inverted condition. Bhatt et al (2005, Experiment 1) then tested 3-month-olds using the same method and clip-art stimuli as those used with 6-month-olds (Bertin & Bhatt, 2004). They found that unlike 6-month-olds, 3-month-olds did not discriminate between the Thatcherized and unaltered faces in either orientation.…”
Section: Thatcher Illusionmentioning
confidence: 94%
See 1 more Smart Citation